Efficacy of a methodology for the scientific development of future physiotherapists - González Méndez, Adrian; Horta Sánchez, Manuel Ernesto; Suárez Pedroso, Maite; Conde Fernández, Berto Delis; Sancho Noriega, Carlomagno; Vílchez Delgado, Rosario Margarita (Horizonte Sanitario, 2025)
Objective: To evaluate the efficacy of a methodology for scientific development in students of the Bachelor’s Degree in Health Rehabilitation at the University of Medical Sciences Sancti Spíritus, Cuba. Materials and methods: Pre-experimental study with 45 third-year students of Rehabilitation in Health (Sancti Spíritus University of Medical Sciences, Cuba, during the 2023-2024 school year). A pedagogical methodology validated by the Delphi method was designed, implementing a guide to academic-work-research tasks. Seven indicators of pre- and post-intervention research skills were evaluated, with statistical analysis using the McNemar-Bowker test. Results: After the application of the methodology, a substantial improvement was observed in the mastery of the investigative skill. Initially, only 4.44% (n=2) of the students were at the "quite adequate" level. After the intervention, this percentage increased significantly to 88.88% (n=40), which demonstrates the effectiveness of the strategy to develop the ability to argue based on the rehabilitation area. The results of the McNemar-Bowker test, with chi-square values between 76.8 and 92.1 (all with p < 0.001), showed significant changes in the distribution of response categories for all indicators. Conclusion: The pre-experiment validates an original methodology that systemically integrates the academic, work, and research dimensions. The results confirm its scientific contribution and practical effectiveness to develop essential research competencies, closing the gap between theoretical training and the demands of professional performance. Keywords: Physical therapy; University students; Professional competence; Rehabilitation Research.